Tropical forage-based systems for climate-smart livestock production in Latin America - Rao, Idupulapati M.; Peters, Michael; Hoek, Rein van der; Castro, A.; Subbaraoa, Guntur V.; Cadisch, Georg; Rincón, A. (2014)
Tropical forage grasses and legumes as key components of sustainable crop-livestock systems in Latin America and the Caribbean have major implications for improving food security, alleviating poverty, restoring degraded lands and mitigating climate change. Climate-smart tropical forage crops can improve the livestock productivity of smallholder farming systems and break the cycle of poverty and resource degradation. Sustainable intensification of forage-based systems contributes to better human nutrition, increases farm incomes, raises soil carbon accumulation and reduces greenhouse gas emissions.